The Computer Reaches Out: The Historical Continuity of Interface Design - Grudin, Jonathan (CHI '90 Proceedings, 1990)
This paper examines the evolution of the focus of user interface research and development from the first production of commercial computer systems in the 1950s through the present. The term “user interface” was not needed in the beginning, when most users were engineers and programmers; it may again become inappropriate when more applications are written for groups than for individuals. But there is a continuity to the outward movement of the computer’s interface to its external environment, from hardware to software to increasingly higher-level cognitive capabilities and finally to social processes. As the focus shifts, the approaches to design and the skills required of practitioners changes. In this paper five foci or levels of development are identified. Most development today is positioned in the third level and considerable research is directed at the fourth. Some attention is now being given to the fifth: repositioning the interface in the work group or organization itself. Work at the different levels is not entirely independent, so establishing a comprehensive framework may enable us to position existing research and development efforts and plan future work more effectively.